(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article presents the results of studies of the level of awareness of parents in the care, upbringing and development of a mentally retarded child. Since the violation of the mental development of the child significantly complicates the game, cognitive, educational, motor and other activities. Therefore, the knowledge of parents, their awareness of the organization and conduct of correctional and developmental work with these children is important for the development of these children in a family environment. The special scientific and methodological literature emphasizes the importance of studying the level of awareness of parents in the upbringing and development of a mentally retarded child in a family environment. However, theoretically and practically, this problem has not been sufficiently studied and developed, which determines the relevance of this study, its theoretical and practical significance. The purpose of the study is to determine the level of awareness of parents in the upbringing and development of children with mental retardation. The results of a sociological survey of 64 parents raising a mentally retarded child showed that in 47% of cases they are not aware of the proper care, upbringing and development of these children in a family environment. It has been established that in different periods of the child’s development, individual parents turn to specialists from both state and non-state organizations. The vast majority of the parents surveyed, in matters of selecting means, methods and conditions for organizing and carrying out work on the care, upbringing and development of a mentally retarded child, rely on their knowledge and work experience. The vast majority of the parents surveyed, in matters of selecting means, methods and conditions for organizing and carrying out work on the care, upbringing and development of a mentally retarded child, rely on their knowledge and work experience. A sociological survey and conversations with parents raising a mentally retarded child showed that the vast majority (61%) of the interviewed parents frankly admitted their unsatisfactory awareness of the care, upbringing, education and development of this child in a family environment. Only 29% of the parents surveyed believe that they have a sufficient level of awareness in these matters, while the rest of the parents found it difficult to answer this question. So, the results of the conducted research allow us to note that, on the one hand, the interviewed parents with a mentally retarded child understand the importance of timely assistance to the child and support for the family, on the other hand, their lack of awareness in the care, upbringing and development of this child makes it difficult to carry out all this family work. In connection with the foregoing, the article highlights the most priority areas of work with a family raising a mentally retarded child and providing parents with information assistance.